Accreditation of Teacher Education by NCATE. A Survey of Opinions Commissioned by the Coordinating Board of the National Council for Accreditation of Teacher Education - Maul, Ray C.; American Association of Colleges for Teacher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
A survey was conducted to determine the attitudes of institutional representatives regarding the efforts of the National Council for Accreditation of Teacher Education (NCATE). Expression regarding NCATE policies, procedures, and standards were sought in questionnaires addressed in April 1969 to the 149 colleges and universities which have participated in the NCATE accreditation or reaccreditation process since the adoption of a revised constitution in 1965. Of the 149, 21 are public universities (90.5 percent replying), 17 private universities, (70.6 percent replying), 56 public colleges (85.7 percent replying), and 55 private colleges (83.6 percent replying). In each of the 120 reporting institutions (in 41 states) the chief administrative officer completed a 16-item questionnaire, and the principal education officer completed a five-part, 38-item instrument to measure opinion on The Institutional Report, the Visiting Team, The Visitation and Appraisal Committee, The Council, and General Considerations. (Brief summary description of the findings is followed by data tables presenting (1) information about the respondents, e.g., accreditation status and relationships with NCATE, (2) number and percent of "yes" and "no" answers and comments on each item, (3) percent of "yes" responses for each type of institution, (4) representative comments for each question.) (JS)
Availability: American Association of Colleges for Teacher Education, 1 Dupont Circle, N.W., Washington, D.C. 20036 ($0.50).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Attitudes; Administrators; Schools of Education; Accreditation (Institutions); Teacher Education